Kontribusi Kepemimpinan Transformasional Kepala Madrasah, Kinerja Mengajar Guru, dan Kultur Belajar Terhadap Peningkatan Prestasi Madrasah Aliyah Negeri Provinsi DKI Jakarta - Darwyan Syah (Jurnal Pendidikan dan Kebudayaan, 2014)
The purpose of this study is to determine the contribution of principal transformational leadership, teaching performance of teachers, and the learning culture towards achievement of madrasah aliyah. Correlational survey is used as the method of the research with 274 sample of teachers .The sampling techniques used are area sampling, proportional sampling and random sampling. Questionnaire used as the instrument to be analyzed by using descriptive and inferential statistics. The results of this study indicate: 1) the level of achievement of the madrasah, principal transformational leadership, teaching performance of teachers and learning culture is good; 2) transformational principal leadership contributes positively and significantly towards achievement of madrasah aliyah; 3) teacher performance in teaching contributes positively and significantly towards achievement of madrasah aliyah; 4) learning culture contributes positively and significantly towards achievement of madrasah aliyah: 5) transformational principal leadership, teacher performance in teaching and learning culture contribute positively and significantly towards achievement of madrasah aliyah. Accordingly, increasing the principal transformational leadership, teaching performance of teachers and the culture of learning leads to the improvement of madrasah achievement.ABSTRAK Tujuan dari penelitian ini untuk menganalisis kontribusi kepemimpinan transformasional kepala madrasah, kinerja mengajar guru, dan kultur belajar terhadap prestasi madrasah aliyah. Metodologi penelitian ini menggunakan survei dengan pendekatan korelasional. Sampel penelitian ini adalah 274 guru dengan teknik pengambilan area sampling, proportional sampling, dan random sampling. Instrumen penelitian menggunakan angket dan analisis data menggunakan statistik deskriptif dan statistik inferensial. Hasil penelitian menunjukkan bahwa: 1) tingkat prestasi madrasah, kepemimpinan transformasional kepala madrasah, kinerja mengajar guru dan kultur belajar berada pada kategori baik; 2) kepemimpinan transformasional kepala madrasah berkontribusi positif dan signifikan terhadap prestasi madrasah aliyah; 3) kinerja mengajar guru berkontribusi positif terhadap prestasi madrasah aliyah; 4) kultur belajar berkontribusi positif dan signifikan terhadap prestasi madrasah aliyah; 5) kepemimpinan transformasional kepala madrasah, kinerja mengajar guru dan kultur belajar berkontribusi positif dan signifikan terhadap prestasi madrasah aliyah. Berdasarkan penelitian yang dilakukan dapat disimpulkan bahwa peningkatan kepemimpinan transformasional kepala madrasah, kinerja mengajar guru, dan kultur belajar meningkatkan prestasi madrasah aliyah.